Glass composition, glass fiber, glass filler, method for producing glass fiber, and method for producing glass filler
By adjusting the component content ratio and mass ratio in the glass composition, the shortcomings of the existing glass composition in terms of elastic modulus, acid resistance and alkali resistance are solved, and a high elasticity and corrosion resistance glass composition is achieved.
Patent Information
- Application Number
- CN202380057942.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-08-04
- Publication Date
- 2025-03-25
AI Technical Summary
There is room for improvement in the elastic modulus, acid resistance and alkali resistance of existing glass compositions.
By adjusting the content of SiO2, Al2O3, B2O3, CaO and T-Fe2O3, and controlling the mass ratio of Al2O3/(SiO2+Al2O3) and MgO/(MgO+CaO), a glass composition with high elastic modulus, improved acid resistance and alkali resistance was prepared.
The high elastic modulus of the glass composition is achieved, and its acid and alkali resistance are improved, making it suitable for reinforced materials of composite materials.
Smart Images

Figure CN119698398A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a glass composition, a glass fiber, a glass filler, a method for producing the glass fiber, and a method for producing the glass filler. Background Art
[0002] Glass, which is made mainly of silicon dioxide (SiO2), has long been used for bottles and window glass. As processing technology has advanced, glass is now widely used as a filler for resins and concrete in the form of glass fibers and flake glass in addition to plate glass.
[0003] The composition of glass has a great influence on the physical properties and chemical resistance of plate glass, glass fibers and flake glass processed from glass.
[0004] For example, E glass, which minimizes the content of alkali components (Na2O, K2O), has excellent electrical insulation, but has the disadvantage of poor acid resistance. In addition, although C glass is envisioned to have higher acid resistance than E glass by increasing the content of Na2O, C glass has poor alkali resistance. Subsequently, alkali-resistant glass (AR glass) was developed, which is characterized by containing ZrO2 as a secondary component.
[0005] AR glass has acid resistance equal to or greater than that of C glass, and also exhibits excellent alkali resistance, so it is suitable as a reinforcing material for concrete. However, AR glass, whose constituent component ZrO2 is more expensive than other glass raw materials, is difficult to be widely used.
[0006] The above-mentioned E glass, C glass and AR glass all have room for improvement in terms of low elastic modulus.
[0007] According to Non-Patent Document 1, E glass, C glass, and AR glass do not contain iron oxide, or the content thereof is less than 1% by mass.
[0008] Patent Document 1 discloses a high elastic composition for glass fiber, which contains SiO2, Al2O3, MgO, Fe2O3, TiO2, CaO and the like as components.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application No. 2020-529378
[0012] Non-patent literature
[0013] Non-patent document 1: Masayuki Yamane et al., “Handbook of Glass Engineering (Popular Edition)”, first edition, Asakura Bookstore Co., Ltd., 1999, p. 514 Summary of the invention
[0014] Problems to be solved by the invention
[0015] Conventional glass compositions are required to have a high elastic modulus and to have improved acid resistance and alkali resistance.
[0016] Therefore, an object of the present invention is to provide a glass composition having a high elastic modulus and improved acid resistance and alkali resistance.
[0017] Means of solving the problem
[0018] As a result of intensive research, the inventors of the present invention discovered that, among the components contained in the glass composition, by appropriately adjusting the contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3, as well as the mass ratios calculated from Al2O3 / (SiO2+Al2O3) and MgO / (MgO+CaO), a glass composition having a high elastic modulus and improved acid resistance and alkali resistance can be obtained, thereby completing the present invention.
[0019] The present inventors have also found that the above-mentioned glass composition can be obtained inexpensively and efficiently by using fly ash as a raw material.
[0020] The present invention provides a glass composition, wherein:
[0021] The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0022] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0023] 0 mass%≤B2O3≤10 mass%,
[0024] 5 mass%≤CaO≤30 mass%,
[0025] 10 mass%<T-Fe2O3≤25 mass%,
[0026] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0027] The mass ratio calculated by MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0028] Furthermore, the present invention provides a glass fiber composed of the above-mentioned glass composition.
[0029] Furthermore, the present invention provides a glass filler, which is composed of the above-mentioned glass composition.
[0030] In addition, the present invention provides a method for manufacturing glass fiber, which comprises the following steps:
[0031] A step of melting the glass composition;
[0032] The molten glass composition is spun to form glass fibers.
[0033] In addition, the present invention provides a method for manufacturing a glass filler, which comprises the following steps:
[0034] A step of melting the glass composition;
[0035] A step of forming the molten glass composition into a glass filler.
[0036] Effects of the Invention
[0037] According to the present invention, a glass composition having a high elastic modulus and improved acid resistance and alkali resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1A This is a perspective view schematically showing an example of glass flakes.
[0039] Figure 1B It is viewed from above Figure 1A A top view of the glass flakes shown.
[0040] Figure 2 This is a schematic diagram for explaining an example of an apparatus and method for producing glass flakes.
[0041] Figure 3 This is a schematic diagram for explaining another example of the apparatus and method for producing glass flakes.
[0042] Figure 4 This is a schematic diagram for explaining an example of a spinning device that can be used to produce chopped strands.
[0043] Figure 5 It is used to illustrate the use of Figure 4 Schematic diagram of an example of an apparatus for producing chopped strands from a wound body of strands obtained from a spinning apparatus shown.
[0044] Fig. 6A This is a perspective view showing an example of a concrete product.
[0045] Figure 6B yes Fig. 6A An enlarged cross-sectional view of a concrete article is shown.
[0046] Figure 7 This is a diagram showing another example of a concrete product.
[0047] Figure 8 This is a diagram showing an example of a rubber belt structure including a rubber reinforcing cord. DETAILED DESCRIPTION
[0048] Hereinafter, the details of the present invention will be described, but the following description is not intended to limit the present invention to specific embodiments.
[0049] [Glass composition]
[0050] <Composition>
[0051] In the glass composition of the present invention, the contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0052] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0053] 0 mass%≤B2O3≤10 mass%,
[0054] 5 mass%≤CaO≤30 mass%,
[0055] 10 mass%<T-Fe2O3≤25 mass%,
[0056] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0057] The mass ratio calculated by MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0058] In addition, iron oxide is usually present in the form of Fe2O3 or FeO in a glass composition. Therefore, the content of iron oxide present as FeO is converted to Fe2O3 and added to the content of iron oxide present as Fe2O3 as the total iron oxide content in the glass composition, which is conventionally expressed as T-Fe2O3.
[0059] In the glass composition of the present invention, SiO2 and Al2O3 are main components that form the skeleton of the glass composition. CaO is a component that suppresses the melt viscosity of the glass composition and is a component that improves the elasticity of the glass composition. Fe2O3 is a component that improves the elasticity of the glass composition. MgO is a component that improves the acid resistance of the glass composition.
[0060] Hereinafter, in this specification, "substantially free" means that the content is less than 0.1 mass %, preferably less than 0.05 mass %, more preferably less than 0.01 mass %, further preferably less than 0.005 mass %, particularly preferably less than 0.003 mass %, and most preferably less than 0.001 mass %. The content, characteristics, and other preferred ranges of each component can adopt any combination of the upper and lower limits described separately below.
[0061] In the present invention, there is no substantial difference between the component ratio in the mixture obtained by blending the raw materials and the component ratio in the glass composition after the mixture is melted. Therefore, the component ratio in the above-mentioned mixture can be regarded as the component ratio of the materials of the glass composition.
[0062] The glass composition of the present invention is obtained by adjusting the blending ratio of raw materials so that the contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3, and the mass ratios of Al2O3 / (SiO2+Al2O3) and MgO / (MgO+CaO) are within the above-mentioned ranges to prepare a mixture, and then pulverizing, melting and solidifying the mixture.
[0063] Hereinafter, each component of the glass composition will be described in detail.
[0064] (SiO2)
[0065] SiO2 is a component that forms the skeleton of the glass composition. In addition, SiO2 is a component that adjusts the devitrification temperature and viscosity when the glass composition is formed, and is also a component that improves the acid resistance of the glass composition. The lower limit of the content of SiO2 in the glass composition is, for example, 45% by mass or more, preferably higher than 45% by mass, 46% by mass or more, 47% by mass or more, 48% by mass or more, 49% by mass or more, 50% by mass or more, 51% by mass or more, 52% by mass or more, 53% by mass or more, 54% by mass or more. The upper limit of the content of SiO2 is, for example, 62% by mass or less, preferably lower than 62% by mass, 60% by mass or less, 59% by mass or less, 58% by mass or less, 57% by mass or less. The content of SiO2 is, for example, 45% by mass ≤ SiO2 ≤ 62% by mass.
[0066] (Al2O3)
[0067] Al2O3 is a component that forms the skeleton of the glass composition. In addition, Al2O3 is a component that adjusts the devitrification temperature and viscosity of the glass composition when it is formed, and is also a component that improves the water resistance of the glass composition. On the other hand, excessive content of Al2O3 will reduce the acid resistance and alkali resistance of the glass composition. The lower limit of the content of Al2O3 is, for example, 3% by mass or more, preferably 4% by mass or more, 4.5% by mass or more, 5% by mass or more, 5.5% by mass or more, and 6% by mass or more. The upper limit of the content of Al2O3 is, for example, 9.5% by mass or less, preferably 9% by mass or less, 8.5% by mass or less, 8% by mass or less, 7.5% by mass or less, and 7% by mass or less.
[0068] (SiO2 + Al2O3)
[0069] In the present invention, the total content of SiO2 and Al2O3 (SiO2 + Al2O3) is very important because it affects the physical properties of the glass composition. As an example, when the (SiO2 + Al2O3) in the glass composition is less than 50 mass% or more than 66 mass%, the viscosity and devitrification temperature increase, and it tends to be difficult to obtain homogeneous glass. In addition, in this case, due to the excessive increase in the melting point of the raw material blend, it tends to be difficult to uniformly maintain the composition of the melt in the melting furnace during mass production of the glass composition using a melting furnace. Therefore, the (SiO2 + Al2O3) in the glass composition is 50 mass% or more and 66 mass% or less. The lower limit of (SiO2 + Al2O3) is, for example, 52 mass% or more, preferably 53 mass% or more, 54 mass% or more, and 55 mass% or more. On the other hand, the upper limit of (SiO2 + Al2O3) is, for example, 65 mass% or less, preferably 64 mass% or less, 63 mass% or less, 62 mass% or less, and 61 mass% or less. In particular, when (SiO 2 + Al 2 O 3 ) is 62 mass % or less, there is a tendency that the working temperature described later can be further reduced in the glass composition.
[0070] (Al2O3 / (SiO2+Al2O3))
[0071] In the glass composition of the present invention, Al2O3 / (SiO2+Al2O3), which is the ratio (quality standard) of the content of Al2O3 to the total content of SiO2 and Al2O3 (SiO2+Al2O3), is 0.05 or more and less than 0.15. When Al2O3 / (SiO2+Al2O3) is less than 0.05 or more than 0.15, the glass composition tends to have poor acid resistance and alkali resistance. In this case, due to the excessive increase in the melting point of the raw material blend, it tends to be difficult to uniformly maintain the composition of the melt in the melting furnace during mass production of the glass composition using a melting furnace. In addition, when Al2O3 / (SiO2+Al2O3) is less than 0.05, there is also a tendency for phase separation to occur easily. The lower limit of Al2O3 / (SiO2+Al2O3) is, for example, 0.06 or more, preferably 0.07 or more, 0.08 or more, 0.09 or more, or 0.10 or more. On the other hand, the upper limit of Al 2 O 3 / (SiO 2 +Al 2 O 3) is, for example, 0.14 or less, preferably 0.13 or less, 0.12 or less, or 0.11 or less.
[0072] (CaO)
[0073] The content of CaO in the glass composition of the present invention is 5% by mass or more and 30% by mass or less. If the content of CaO in the glass composition is less than 5% by mass, the devitrification temperature becomes high, and there is a tendency to be difficult to obtain homogeneous glass. On the other hand, if it is higher than 30% by mass, the viscosity of the melt is too low, and there is a tendency to lack formability. The lower limit of the content of CaO is, for example, 8% by mass or more, preferably 10% by mass or more, 12% by mass or more, 13% by mass or more, 14% by mass or more, 15% by mass or more, 16% by mass or more, 17% by mass or more, 18% by mass or more, 19% by mass or more, and 20% by mass or more. On the other hand, the upper limit of the content of CaO is, for example, 28% by mass or less, preferably 26% by mass or less, 25% by mass or less, and 24% by mass or less.
[0074] (Fe2O3)
[0075] In the glass composition of the present invention, Fe2O3 plays an important role. That is, if Fe2O3 is contained in the glass composition in an appropriate range, the acid resistance and alkali resistance of the glass composition are improved. In addition, Fe2O3 increases the elastic modulus of the glass composition. On the other hand, if Fe2O3 is excessively contained in the glass composition, the acid resistance and alkali resistance are reduced, and devitrification occurs. Therefore, the content of T-Fe2O3 (total iron oxide converted to Fe2O3) in the glass composition is higher than 10 mass% and lower than 25 mass%. The lower limit of the content of T-Fe2O3 in the glass composition is, for example, 10.1 mass% or more, preferably 10.5 mass% or more, 11 mass% or more, 12 mass% or more, 13 mass% or more, 14 mass% or more, 15 mass% or more, 15.5 mass% or more, and 16 mass% or more. The upper limit of the content of T-Fe2O3 is, for example, 23 mass % or less, preferably 21 mass % or less, 20 mass % or less, 19 mass % or less, or 18 mass % or less. The content of T-Fe2O3 is, for example, 11 mass % ≤ T-Fe2O3 ≤ 25 mass %.
[0076] (MgO)
[0077] The glass composition of the present invention contains MgO. By containing an appropriate amount of MgO, the acid resistance of the glass composition is improved. However, excessive MgO content tends to cause the glass composition to be easily devitrified, and the alkali resistance of the glass composition tends to be reduced. The glass composition of the present invention tends to have a high elastic modulus because the content of Fe2O3 and the content of MgO are appropriately adjusted. The lower limit of the content of MgO is, for example, 0.01 mass% or more, preferably 0.05 mass% or more, 0.1 mass% or more, 0.15 mass% or more, and 0.2 mass% or more. In addition, the upper limit of the content of MgO is, for example, 10 mass% or less, preferably 8 mass% or less, 6 mass% or less, 5 mass% or less, 4 mass% or less, 3 mass% or less, and 2 mass% or less. The content of MgO is, for example, 0.1 mass%≤MgO≤10 mass%.
[0078] (MgO + CaO)
[0079] In the present invention, the total content of MgO and CaO (MgO + CaO) affects the physical properties of the glass composition. As an example, when (MgO + CaO) in the glass composition is less than 5 mass%, there is a tendency that the devitrification temperature becomes high and it is difficult to obtain homogeneous glass. On the other hand, when (MgO + CaO) is higher than 30 mass%, the viscosity of the melt is too low and the formability deteriorates. The lower limit of (MgO + CaO) is, for example, 5 mass% or more, preferably 8 mass% or more, 10 mass% or more, 11 mass% or more, 12 mass% or more, 13 mass% or more, 14 mass% or more, 15 mass% or more, 16 mass% or more, 17 mass% or more, 18 mass% or more, 19 mass% or more, 20 mass% or more, 20.1 mass% or more, 20.2 mass% or more. On the other hand, the upper limit of (MgO+CaO) is, for example, 30 mass % or less, preferably 28 mass % or less, 27 mass % or less, 26 mass % or less, 25 mass % or less, 24.5 mass % or less, or 24 mass % or less.
[0080] (MgO / (MgO + CaO))
[0081] In the glass composition of the present invention, MgO / (MgO+CaO), which is the ratio (by mass) of the content of MgO to the total content of MgO and CaO (MgO+CaO), is 0.001 or more and 0.20 or less. If MgO / (MgO+CaO) is higher than 0.20, devitrification tends to occur easily, and the alkali resistance of the glass composition tends to decrease. On the other hand, if MgO / (MgO+CaO) is lower than 0.001, the effect of improving the acid resistance by containing MgO tends to be insufficient. The lower limit of MgO / (MgO+CaO) is, for example, 0.002 or more, preferably 0.003 or more, 0.004 or more, 0.005 or more, 0.006 or more, 0.007 or more, 0.008 or more, 0.009 or more, 0.01 or more, 0.011 or more, 0.012 or more, 0.013 or more, 0.014 or more, 0.015 or more, 0.016 or more, 0.017 or more, 0.018 or more, 0.019 or more, or 0.02 or more. On the other hand, the upper limit of MgO / (MgO+CaO) is, for example, 0.18 or less, preferably 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. According to the above, the upper limit of MgO / (MgO+CaO) may be 0.05 or less, 0.02 or less, 0.015 or less, or 0.01 or less.
[0082] The glass composition of the present invention may contain the following components in addition to the above components.
[0083] (B2O3)
[0084] B2O3, like SiO2 and Al2O3, can form the skeleton of the glass composition. By making the glass composition contain B2O3, the viscosity during melting can be set in a range suitable for glass manufacturing. Therefore, the glass composition of the present invention may also contain B2O3. However, if the glass composition contains B2O3 excessively, it shows a tendency to reduce acid resistance and alkali resistance, and devitrification and phase separation occur. The content of B2O3 in the glass composition of the present invention is more than 0 mass% and less than 10 mass%. The lower limit of the content of B2O3 is, for example, more than 0.1 mass%, preferably more than 0.2 mass%. In addition, the upper limit of the content of B2O3 is, for example, less than 8 mass%, preferably less than 6 mass%, less than 4 mass%, less than 2 mass%, and less than 1 mass%. The content of B2O3 can be 0.1 mass%≤B2O3≤10 mass%. In addition, B2O3 may be substantially free of B2O3.
[0085] (SiO2 + B2O3)
[0086] In the present invention, the total content of SiO2 and B2O3 (SiO2 + B2O3) affects the physical properties of the glass composition. As an example, when (SiO2 + B2O3) in the glass composition is less than 50% by mass or greater than 66% by mass, the devitrification temperature becomes high and it is difficult to obtain homogeneous glass. In addition, in this case, since the melting point of the raw material blend is excessively increased, it is difficult to uniformly maintain the composition of the melt in the melting furnace during mass production of the glass composition using a melting furnace. Therefore, the (SiO2 + B2O3) in the glass composition is preferably greater than 50% by mass and less than 66% by mass. The lower limit of (SiO2 + B2O3) is, for example, greater than 52% by mass, preferably greater than 53% by mass, greater than 54% by mass, and greater than 55% by mass. On the other hand, the upper limit of (SiO2+B2O3) is, for example, 65 mass % or less, preferably 64 mass % or less, 63 mass % or less, 62 mass % or less, 61 mass % or less, 60 mass % or less, 59 mass % or less, 58 mass % or less, or 57 mass % or less.
[0087] (Li2O, Na2O, K2O)
[0088] Alkali metal oxides (Li2O, Na2O, K2O) lower the melting point of the glass composition and improve the fluidity of the melt. Therefore, in mass production of glass compositions using a melting furnace, they play an effect of uniformly maintaining the composition of the melt in the melting furnace. Therefore, the glass composition of the present invention can contain an appropriate amount of alkali metal oxides (Li2O, Na2O, K2O). However, if excessively contained, Young's modulus and alkali resistance may decrease, and devitrification may also occur.
[0089] The upper limit of the Li2O content is, for example, 5 mass % or less, preferably 4 mass % or less, 3 mass % or less, 2 mass % or less, less than 1 mass %, 0.9 mass % or less, 0.8 mass % or less, 0.7 mass % or less, 0.6 mass % or less, or 0.5 mass % or less.
[0090] The lower limit of the content of Na2O is, for example, 0.01% by mass or more, preferably 0.05% by mass or more, 0.1% by mass or more, and 0.2% by mass or more. The upper limit of the content of Na2O is, for example, 5% by mass or less, preferably 4% by mass or less, 3% by mass or less, 2% by mass or less, less than 1% by mass, 0.9% by mass or less, 0.8% by mass or less, 0.7% by mass or less, 0.6% by mass or less, and 0.5% by mass or less.
[0091] The lower limit of the content of K2O is, for example, 0.05 mass % or more, preferably 0.1 mass % or more, 0.2 mass % or more. The upper limit of the content of K2O is, for example, 5 mass % or less, preferably 4 mass % or less, less than 3 mass %, 2 mass % or less, less than 1 mass %, 0.9 mass % or less, 0.8 mass % or less, 0.7 mass % or less, 0.6 mass % or less, 0.5 mass % or less.
[0092] The lower limit of the total content of Na2O and K2O (Na2O+K2O) is, for example, 0.1 mass % or more, preferably 0.2 mass % or more. The upper limit of (Na2O+K2O) is, for example, 5 mass % or less, preferably 4 mass % or less, 3 mass % or less, 2 mass % or less, less than 1 mass %, 0.9 mass % or less, or 0.8 mass % or less.
[0093] The lower limit of the total content of alkali metal oxides (Li2O+Na2O+K2O) is, for example, 0.1 mass % or more, preferably 0.2 mass % or more. The upper limit of (Li2O+Na2O+K2O) is, for example, 5 mass % or less, preferably 4 mass % or less, 3 mass % or less, 2 mass % or less, less than 1 mass %, 0.9 mass % or less, 0.8 mass % or less. The content of Li2O, Na2O and K2O is, for example, 0.1 mass %≤Li2O+Na2O+K2O≤5 mass %.
[0094] (SrO)
[0095] The glass composition of the present invention may contain SrO. By making the glass composition contain SrO, the devitrification temperature and viscosity during melting can be set in a range suitable for glass manufacturing. On the other hand, if the glass composition contains SrO excessively, the Young's modulus, acid resistance and alkali resistance of the glass composition are reduced. Therefore, the upper limit of the content of SrO in the glass composition is, for example, 15% by mass or less, preferably 12% by mass or less, 10% by mass or less, 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.1% by mass or less. It is also possible to substantially not contain SrO. Depending on the circumstances, the lower limit of the content of SrO is, for example, 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more. The content of SrO can be 0.1% by mass ≤ SrO ≤ 10% by mass.
[0096] (BaO)
[0097] The glass composition of the present invention may contain BaO. By making the glass composition contain BaO, the devitrification temperature and viscosity during melting can be set within a range suitable for glass production. On the other hand, if the glass composition contains BaO excessively, the Young's modulus, acid resistance, and alkali resistance of the glass composition are reduced. Therefore, the upper limit of the content of BaO in the glass composition is, for example, 10% by mass or less, preferably 8% by mass or less, 6% by mass or less, 4% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, and 0.1% by mass or less. It is also possible to contain substantially no BaO.
[0098] (ZnO)
[0099] The glass composition of the present invention may contain ZnO. By making the glass composition contain ZnO, the devitrification temperature and viscosity during melting can be set within a range suitable for glass manufacturing. On the other hand, if the glass composition contains ZnO excessively, the Young's modulus, acid resistance and alkali resistance of the glass composition are reduced. Therefore, the upper limit of the content of ZnO in the glass composition is, for example, 10% by mass or less, preferably 8% by mass or less, 6% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, and 0.1% by mass or less. ZnO may also be substantially absent.
[0100] (TiO2)
[0101] The glass composition of the present invention may contain TiO2. By making the glass composition contain TiO2, the viscosity during melting can be set in a range suitable for glass manufacturing. On the other hand, if the glass composition contains TiO2 excessively, it is easy to lose transparency. Therefore, the upper limit of the content of TiO2 in the glass composition is, for example, 10% by mass or less, preferably 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, and 0.5% by mass or less. The lower limit of the content of TiO2 is, for example, 0.1% by mass or more, and may also be 0.2% by mass or more. It may also be substantially free of TiO2. The content of TiO2 can be 0.1% by mass ≤ TiO2 ≤ 10% by mass.
[0102] (ZrO2)
[0103] The glass composition of the present invention may contain ZrO2. By making the glass composition contain ZrO2, the viscosity during melting can be set in a range suitable for glass manufacturing. On the other hand, if the glass composition contains ZrO2 excessively, it is easy to lose transparency. Therefore, the upper limit of the content of ZrO2 in the glass composition is, for example, 10% by mass or less, preferably 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.1% by mass or less. ZrO2 may also be substantially absent. Depending on the circumstances, the lower limit of the content of ZrO2 may be, for example, 0.1% by mass or more, or 0.2% by mass or more. The content of ZrO2 may be 0.1% by mass ≤ ZrO2 ≤ 10% by mass.
[0104] (MnO2)
[0105] The glass composition of the present invention may contain MnO2. By making the glass composition contain MnO2, the viscosity during melting can be set within a range suitable for glass manufacturing. On the other hand, if the glass composition contains MnO2 excessively, it is easy to lose clarity. Therefore, the upper limit of the content of T-MnO2 (total manganese oxide converted to MnO2) in the glass composition is, for example, 5% by mass or less, preferably 2% by mass or less, 1% by mass or less, 0.5% by mass or less, or 0.1% by mass or less. T-MnO2 may also be substantially absent.
[0106] (Other ingredients)
[0107] The glass composition of the present invention may contain at least one selected from the group consisting of P2O5, PbO, Bi2O3, La2O3, WO3, Nb2O5, Y2O3, MoO3, Ta2O5, Cr2O3, CuO and CoO as other components at a content of 0% to 5% by mass. The allowable content of each of these components is, for example, less than 2% by mass, less than 1% by mass, less than 0.5% by mass, or less than 0.1% by mass. The total allowable content of these components is, for example, less than 5% by mass, less than 2% by mass, less than 1% by mass, less than 0.5% by mass, or less than 0.1% by mass. However, the above other components may not be substantially contained.
[0108] The glass composition of the present invention may contain at least one selected from the group consisting of SO3, F2, Cl2, Br2, I2, SnO2, CeO2, As2O3 and Sb2O3 as an additive at a content of 0 mass % or more and 1 mass % or less. The allowable content of each of these components is, for example, less than 0.5 mass %, less than 0.2 mass %, or less than 0.1 mass %. The total allowable content of these components is, for example, less than 1 mass %, less than 0.5 mass %, less than 0.2 mass %, or less than 0.1 mass %. However, the above-mentioned additives may not be substantially contained.
[0109] The glass composition of the present invention may contain at least one selected from the group consisting of H2O, OH, H2, CO2, CO, He, Ne, Ar, and N2 at a content of 0% to 0.1% by mass. The allowable content of each of these components is, for example, less than 0.05% by mass, less than 0.03% by mass, or less than 0.01% by mass. The total allowable content of these components is, for example, less than 0.1% by mass, less than 0.05% by mass, less than 0.03% by mass, or less than 0.01% by mass. However, each of the above components may be substantially free of them.
[0110] The glass composition of the present invention may also contain a trace amount of precious metal elements. For example, precious metal elements such as Pt, Rh, Au, and Os may be contained at a content of 0 mass % or more and 0.1 mass % or less. The allowable content of these components is, for example, less than 0.1 mass %, less than 0.05 mass %, less than 0.03 mass %, or less than 0.01 mass %. The total allowable content of these components is, for example, less than 0.1 mass %, less than 0.05 mass %, less than 0.03 mass %, or further less than 0.01 mass %. However, the above-mentioned precious metal elements may be substantially absent.
[0111] In a preferred example of the glass composition of the present invention,
[0112] The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0113] 45 mass%≤SiO2≤62 mass%,
[0114] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0115] 0 mass%≤B2O3≤10 mass%,
[0116] 5 mass%≤CaO≤30 mass%,
[0117] 10 mass%<T-Fe2O3≤25 mass%,
[0118] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0119] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0120] In another preferred example of the glass composition of the present invention,
[0121] The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0122] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0123] 0.1 mass%≤B2O3≤10 mass%,
[0124] 5 mass%≤CaO≤30 mass%,
[0125] 10 mass%<T-Fe2O3≤25 mass%,
[0126] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0127] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0128] In another preferred example of the glass composition of the present invention,
[0129] The contents of SiO2, Al2O3, B2O3, MgO, CaO and T-Fe2O3 are as follows:
[0130] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0131] 0 mass%≤B2O3≤10 mass%,
[0132] 0.1 mass%≤MgO≤10 mass%,
[0133] 5 mass%≤CaO≤30 mass%,
[0134] 10 mass%<T-Fe2O3≤25 mass%,
[0135] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0136] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0137] In another preferred example of the glass composition of the present invention,
[0138] The contents of SiO2, Al2O3, B2O3, CaO, TiO2 and T-Fe2O3 are as follows:
[0139] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0140] 0 mass%≤B2O3≤10 mass%,
[0141] 5 mass%≤CaO≤30 mass%,
[0142] 0.1 mass%≤SrO≤15 mass%
[0143] 10 mass%<T-Fe2O3≤25 mass%,
[0144] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0145] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0146] In another preferred example of the glass composition of the present invention,
[0147] The contents of SiO2, Al2O3, B2O3, CaO, TiO2 and T-Fe2O3 are as follows:
[0148] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0149] 0 mass%≤B2O3≤10 mass%,
[0150] 5 mass%≤CaO≤30 mass%,
[0151] 0.1 mass%≤TiO2≤10 mass%,
[0152] 10 mass%<T-Fe2O3≤25 mass%,
[0153] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0154] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0155] In another preferred example of the glass composition of the present invention,
[0156] The contents of SiO2, Al2O3, B2O3, CaO, ZrO2 and T-Fe2O3 are as follows:
[0157] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0158] 0 mass%≤B2O3≤10 mass%,
[0159] 5 mass%≤CaO≤30 mass%,
[0160] 0.1 mass%≤ZrO2≤10 mass%
[0161] 10 mass%<T-Fe2O3≤25 mass%,
[0162] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0163] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0164] In another preferred example of the glass composition of the present invention,
[0165] The contents of SiO2, Al2O3, B2O3, CaO, Li2O, Na2O, K2O and T-Fe2O3 are as follows:
[0166] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0167] 0 mass%≤B2O3≤10 mass%,
[0168] 5 mass%≤CaO≤30 mass%,
[0169] 0.1 mass%≤Li2O+Na2O+K2O≤5 mass%,
[0170] 10 mass%<T-Fe2O3≤25 mass%,
[0171] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0172] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0173] In another preferred example of the glass composition of the present invention,
[0174] The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0175] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0176] 0 mass%≤B2O3≤10 mass%,
[0177] 50 mass%≤SiO2+B2O3≤66 mass%,
[0178] 5 mass%≤CaO≤30 mass%,
[0179] 10 mass%<T-Fe2O3≤25 mass%,
[0180] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0181] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0182] In another preferred example of the glass composition of the present invention,
[0183] The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are as follows:
[0184] 50 mass%≤SiO2+Al2O3≤66 mass%,
[0185] 0 mass%≤B2O3≤10 mass%,
[0186] 5 mass%≤CaO≤30 mass%,
[0187] 11 mass%≤T-Fe2O3≤25 mass%,
[0188] The mass ratio calculated by Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15,
[0189] The mass ratio calculated as MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
[0190] <Glass materials>
[0191] When obtaining the glass composition of the present invention, there is no restriction on the raw materials as long as it is included in the above composition range. In particular, fly ash is preferably used as a part of the raw materials. In other words, the glass composition of the present invention preferably contains fly ash as a raw material. However, fly ash may not be used.
[0192] <Features>
[0193] Hereinafter, the properties of the glass composition of the present invention will be described.
[0194] (Young's modulus)
[0195] For glass compositions, the higher the Young's modulus, the better the elasticity. According to a glass composition with a high Young's modulus, the mechanical properties of a composite material reinforced by glass fiber and glass filler can be improved. Here, the Young's modulus (GPa) can be obtained by measuring the longitudinal wave velocity and the transverse wave velocity of elastic waves propagating in the glass by a conventional ultrasonic method, based on these velocities and the density of the glass measured separately by the Archimedean method. The lower limit of the Young's modulus is, for example, above 85 GPa, and can also be above 86 GPa, above 87 GPa, above 88 GPa, and above 89 GPa. The upper limit of the Young's modulus is, for example, below 100 GPa, and can also be below 99 GPa, below 98 GPa, below 97 GPa, below 96 GPa, below 95 GPa, and below 94 GPa.
[0196] (Glass transition temperature)
[0197] The glass transition temperature (glass transition point) is an indicator of the heat resistance of glass. The lower limit of the glass transition temperature may be 560°C or higher, 580°C or higher, 600°C or higher, 610°C or higher, 620°C or higher, 630°C or higher, 640°C or higher, 650°C or higher, 660°C or higher, and further 670°C or higher. The upper limit of the glass transition temperature may be 800°C or lower, 780°C or lower, 760°C or lower, 750°C or lower, 740°C or lower, and further 730°C or lower.
[0198] (Melting characteristics)
[0199] The temperature at which the viscosity of molten glass reaches 1000 dPa·sec (1000 poise) is called the working temperature of the glass, and is the most suitable temperature for forming glass fibers and glass fillers. When manufacturing flaky glass or glass fibers as glass fibers and glass fillers, if the working temperature of the glass is 1000°C or higher, the thickness of the flaky glass or the deviation of the diameter of the glass fibers can be reduced. If the working temperature is 1450°C or lower, the fuel cost during glass melting can be reduced, the glass manufacturing equipment is less susceptible to thermal corrosion, and the equipment life is extended. The lower limit of the working temperature is, for example, 1000°C or higher, and may be 1050°C or higher, or 1100°C or higher. The upper limit of the working temperature is, for example, 1450°C or lower, and may be 1400°C or lower, 1350°C or lower, 1300°C or lower, 1250°C or lower, 1200°C or lower, 1190°C or lower, 1180°C or lower, 1170°C or lower, 1160°C or lower, 1150°C or lower, or 1140°C or lower.
[0200] (Chemical durability)
[0201] As an indicator of acid resistance, the mass loss rate ΔW1 described later is used, and the smaller the ΔW1, the higher the acid resistance. When the glass composition is used as a reinforcing material for a composite material, the ΔW1 of the glass composition is preferably 0.50 mass % or less. The ΔW1 of the glass composition of the present invention is, for example, 0.40 mass % or less, preferably 0.30 mass % or less, 0.20 mass % or less, 0.17 mass % or less, 0.15 mass % or less, 0.10 mass % or less, and more preferably 0.05 mass % or less. The lower limit of ΔW1 is not particularly limited, and is, for example, 0.02 mass % or more.
[0202] As an index of alkali resistance, the mass loss rate ΔW2 described later is used, and the smaller the ΔW2, the higher the alkali resistance. When the glass composition is used as a reinforcing material for a composite material, the ΔW2 of the glass composition is preferably 0.50 mass % or less. The ΔW2 of the glass composition of the present invention is, for example, 0.40 mass % or less, preferably 0.30 mass % or less, 0.20 mass % or less, 0.18 mass % or less, 0.15 mass % or less, 0.10 mass % or less, and more preferably 0.05 mass % or less. The lower limit of ΔW2 is not particularly limited, and is, for example, 0.03 mass % or more.
[0203] [Glass fiber]
[0204] The glass fiber of this embodiment is composed of the above-mentioned glass composition. The glass fiber of this embodiment can be a long glass fiber or a short glass fiber. Since the short glass fiber has a cotton-like shape, it is also called glass wool. The average fiber diameter of the glass fiber is, for example, 0.1 to 50 μm.
[0205] The manufacturing method of the glass fiber of the present embodiment includes a process of melting the above-mentioned glass composition and a process of spinning the molten glass composition to form glass fibers. As an example, long glass fibers are manufactured by making a glass melt with controlled viscosity flow out from a nozzle and winding it up by a winder. The continuous fiber is cut into appropriate lengths when used. Short glass fibers are manufactured by blowing the glass melt while using high-pressure air, centrifugal force, etc.
[0206] [Glass filler]
[0207] The glass filler of this embodiment is composed of the above-mentioned glass composition. The form of the glass filler is not particularly limited. The glass filler can be at least one selected from flaky glass, chopped strands, milled fibers, glass powder and glass beads. However, these forms are not strictly distinguished from each other. The glass filler of this embodiment can also be composed of two or more glass fillers with different forms.
[0208] The method for producing a glass filler according to the present embodiment includes a step of melting the above-mentioned glass composition and a step of shaping the molten glass composition into a glass filler. Hereinafter, various forms of the glass filler will be described.
[0209] A preferred example of the glass filler of the present embodiment is glass flakes. Glass flakes have a thin sheet shape and are also called thin sheet glass. Figure 1A and Figure 1B An example of glass flake is shown. Figure 1A The average thickness t of the glass flake 1 shown is, for example, 0.1 to 15 μm. The average particle size is, for example, 0.2 to 15000 μm. The aspect ratio of the glass flake 1 is, for example, 2 to 1000. The aspect ratio can be obtained by dividing the average particle size by the average thickness t.
[0210] The glass flake 1 can be used, for example, Figure 2 The device shown was fabricated. Figure 2 In the apparatus shown, the glass material 11 melted in the refractory furnace 12 is expanded into a balloon shape by the gas fed into the blowing nozzle 15 to form a hollow glass film 16. Then, the hollow glass film 16 is crushed by the pressing roller 17 to obtain the glass flakes 1.
[0211] The glass flake 1 can also be used, for example Figure 3 The device shown was fabricated. Figure 3In the device shown, the molten glass raw material 11 flowing into the rotating cup 22 from the nozzle 21 flows out radially from the upper edge of the cup 22 by the centrifugal force generated by the rotation of the rotating cup 22. The flowing raw material 11 passes through the annular plates 23 arranged above and below, is sucked by the air flow, and is introduced into the annular cyclone type collector 24. While passing through the annular plates 23, the glass is cooled and solidified into a thin film, and is further broken into fine fragments to obtain flaky glass 1.
[0212] Another preferred example of the glass filler of the present embodiment is chopped strands. Chopped strands have a shape obtained by cutting glass fibers short. The fiber diameter of the chopped strands is, for example, 1 to 50 μm, and the aspect ratio thereof is, for example, 2 to 10,000. The aspect ratio of the chopped strands can be obtained by dividing the fiber length by the fiber diameter.
[0213] Chopped strands, for example, can be used Figure 4 and Figure 5 The device shown is manufactured. First, Figure 4 As shown, the glass raw material with a prescribed composition melted in the refractory kiln is pulled out from a leak plate 30 having a plurality of (e.g., 2,400) nozzles at the bottom to form a plurality of glass filaments 31. After cooling water is sprayed on the glass filaments 31, an adhesive (bundling agent) 34 is applied by a coating roller 33 of an adhesive applicator 32. The plurality of glass filaments 31 coated with the adhesive 34 are bundled by a reinforcing mat 35 to form, for example, a strand 36 consisting of about 800 glass filaments 31. Each strand 36 is wound around a cylindrical tube 39 embedded in a chuck 38 while being cross-swung by a traverse finger 37. Then, the cylindrical tube 39 wound with the strand 36 is removed from the chuck 38 to obtain a strand cake (strand winding body) 40.
[0214] Then, if Figure 5 As shown, a yarn cake 40 is stored in a creel 41, and the raw yarn 36 is pulled out from the yarn cake 40 and gathered into a raw yarn bundle 43 by a bundle guide 42. Water or a treatment liquid is sprayed on the raw yarn bundle 43 by a spray device 44. In addition, the raw yarn bundle 43 is cut by a rotating blade 46 of a cutting device 45 to obtain a chopped strand 47.
[0215] Another preferred example of the glass filler of this embodiment is milled fiber. The milled fiber has a shape obtained by cutting glass fiber into powder. The fiber diameter of the milled fiber is, for example, 1 to 50 μm, and its aspect ratio is, for example, 2 to 500. The aspect ratio of the milled fiber can be obtained by dividing the fiber length by the fiber diameter. The milled fiber can be obtained by a known method.
[0216] Another preferred example of the glass filler of this embodiment is glass powder. Glass powder is powdered glass, which is produced by crushing glass. The average particle size of the glass powder is, for example, 1 to 500 μm. The particle size of the glass powder is defined as the diameter of a sphere having the same volume as the particles of the glass powder. The glass powder can be obtained by a known method.
[0217] Another preferred example of the glass filler of this embodiment is glass beads. The glass beads have a spherical or substantially spherical shape. The average particle size of the glass beads is, for example, 1 to 500 μm. The particle size of the glass beads is defined as the diameter of a sphere having the same volume as the particles of the glass beads. The glass beads can be obtained by a known method.
[0218] [Applications of glass fiber and glass filler]
[0219] The glass fiber and glass filler of this embodiment can be used to reinforce various products. For example, the glass fiber and glass filler can be used to reinforce concrete products, rubber products, or plastic products.
[0220] <Reinforcement of concrete products>
[0221] As described above, glass fibers and glass fillers can be used to reinforce concrete products. From another aspect, the present invention provides a concrete product having at least one selected from the group consisting of glass fibers and glass fillers of this embodiment. In a preferred embodiment, the concrete product has a cement composition, and glass fibers or glass fillers embedded in the cement composition. In another preferred embodiment, the concrete product has a main body, and a covering member covering the surface of the main body, and the covering member contains glass fibers or glass fillers. The covering member may also contain materials such as resin and cement.
[0222] Glass fillers (especially chopped strands) can also be used to reinforce concrete products. Glass fibers and glass fillers used to reinforce concrete products can be processed appropriately according to the type of concrete products. In detail, fiber sheets and rods containing glass fibers and glass fillers can also be used to reinforce concrete products.
[0223] (Chopped Strand)
[0224] Chopped strands, for example, can be mixed with cement compositions. In addition, chopped strands can be classified into "bundled chopped strands" formed by strand bundles, and "non-bundled chopped strands" formed by one strand. As an example, a mixture of non-bundled chopped strands and a cement composition can be sprayed on the surface of the main body of a concrete product to form a covering member covering the surface of the main body. According to the covering member, it is possible to suppress the concrete material from peeling off from the surface of the main body. On the other hand, the mixture of bundled chopped strands and a cement composition is suitable for reinforcing the entire concrete product. The bundled chopped strands in the mixture play the same role as the straw used in earth walls and mortar.
[0225] The chopped strands have a large specific surface area and a large contact area with cement. Therefore, it is particularly preferred that the chopped strands used for the reinforcement of concrete products have excellent alkali resistance. The chopped strands also need to have a sufficient elastic modulus for practical use.
[0226] (Fiber sheet)
[0227] The fiber sheet may be a woven fabric or a nonwoven fabric. As a woven fabric, for example, a fabric using roving and yarn as warp and / or weft may be cited. As a nonwoven fabric, for example, a chopped strand mat formed of chopped strands may be cited. The nonwoven fabric may also be formed of short fiber glass fibers.
[0228] The fiber sheet can be used by impregnating a resin such as cement mortar and epoxy resin. The fiber sheet can also be used in a state where the surface thereof is covered with a layer (resin layer) composed of a resin. In this specification, a fiber sheet impregnated with cement mortar and a resin and a fiber sheet whose surface is covered with a resin layer are referred to as a protective sheet. The protective sheet can be manufactured by a known method such as a hand lay-up molding method, an SMC (Sheet Molding Compound) molding method, or a BMC (Bulk Molding Compound) molding method.
[0229] Fig. 6A and 6B An example of a concrete product including the above-mentioned protective sheet is shown. Fig. 6A and 6B In the figure, as a concrete product, a segment 51 for lining a tunnel formed by a shield construction method is shown. The segment 51 has an arc plate shape and can be joined together to form a cylindrical lining body in a borehole excavated by a shield machine. In detail, a plurality of segments 51 can be joined together in the circumferential direction to form a ring. A plurality of segments 51 can be joined together in the axial direction of the ring to form a lining body.
[0230] A joint plate 53 is provided on the circumferential joint end surface 51A of the arch 51. By fastening the joint plates 53 to each other, the plurality of arches 51 are fixed, thereby enabling the plurality of arches 51 to be joined in the circumferential direction. A joint rod (not shown) protruding from the joint end surface 51B is provided on one joint end surface 51B of the arch 51 in the axial direction of the ring. A joint member 52 is provided on the other joint end surface 51B to engage with the joint rod. An insertion hole H is formed on the joint member 52 to insert the joint rod.
[0231] Figure 6B FIG. 5 is an enlarged cross-sectional view of the arcuate body 51 near the joint end surface 51B. Figure 6B As shown in FIG. 1 , the arch 51 further includes a protective sheet 61 disposed on the joint end surface 51B. In other words, in the arch 51, the surface of the protective sheet 61 constitutes the joint end surface 51B. The protective sheet 61 functions as a covering member covering the surface of the main body of the arch 51. When a plurality of arches 51 are joined together, the joint end surfaces 51B, i.e., the protective sheets 61, are in contact with each other.
[0232] like Fig. 6A and 6B As shown, the segment 51 may further include a sealing member 64 for sealing the segment 51 when the plurality of segment 51 are joined to each other.
[0233] In the shield construction method, the shield machine digs the foundation with the cutter at its front end while extending the top rod of the jack so that the spreader of the jack is in contact with the lining body formed by the bow 51. As a result, the shield machine can obtain a reaction force from the lining body through the jack and can be propelled by means of the reaction force. Because the shield machine is equipped with multiple jacks, multiple spreaders are in contact with the lining body. Therefore, when the pressing force applied to the lining body from the multiple spreaders acts toward the outside of the lining body, stress is generated between two adjacent bows 51 in the lining body. The protective sheet 61 can suppress the occurrence of cracks near the joint end face 51B by buffering this stress.
[0234] (Rod)
[0235] The rod is, for example, a bundle of glass fibers. As an example, the rod is made by weaving glass fibers into a braided cable. In the rod, the bundled glass fibers can also be cured by a resin such as cement or epoxy resin. The rod can be used instead of steel bars, for example.
[0236] Figure 7 An example of a concrete product including the above-mentioned rod is shown. Figure 7As a concrete product, a utility pole 70 is shown. A portion of the utility pole 70 is buried in the ground 80 and extends upward. The utility pole 70 includes: a cement composition 72 containing mortar and the like filled inside; and a plurality of rods 75 buried in the cement composition 72. The rods 75 are arranged parallel to each other from the bottom of the utility pole 70 along the direction in which the utility pole 70 extends. It is particularly preferred that the glass fiber has an excellent elastic modulus in the rod 75 used for reinforcing the utility pole 70. The glass fiber also needs to have sufficient alkali resistance for practical use.
[0237] Figure 7 The utility pole 70 shown can be produced, for example, by inserting a rod 75 into the interior of a utility pole having a cavity formed therein through an opening, etc., and then filling the interior of the utility pole with a cement composition 72. The details of the production method are described, for example, in Japanese Patent Publication No. 2006-2543. In Japanese Patent Publication No. 2006-2543, an aramid rod formed of aramid fiber is used. The rod 75 containing the glass fiber of this embodiment tends to have better alkali resistance than the aramid rod.
[0238] (other)
[0239] Examples of concrete products reinforced by glass fibers or glass fillers are not limited to the above. Glass fibers and glass fillers can be used as aggregates, reinforcing materials, etc. of various concrete products. Because glass fibers and glass fillers also have good mechanical properties and a tendency to thermal stability, they can also be used for concrete products requiring heat resistance (for example, concrete products used in power plants, smelting furnaces, coke ovens, etc.) or building materials requiring fire resistance (for example, fire-resistant structures of buildings, fire-resistant coating materials, etc.).
[0240] In addition, glass fiber and glass filler can be processed into other forms besides the above-mentioned chopped strands, fiber sheets, and rods, such as raw yarns, rovings, yarns, ropes, etc. In addition, yarns are obtained by twisting one or more strands.
[0241] <Reinforcement of rubber products>
[0242] As mentioned above, glass fibers and glass fillers can also be used to reinforce rubber products. From another aspect, the present invention provides a rubber product, which has at least one selected from the group consisting of glass fibers and glass fillers of this embodiment. As an example, the rubber product has a rubber composition (base rubber) and glass fibers or glass fillers embedded in the rubber composition.
[0243] The glass fiber and glass filler used for reinforcing rubber products can be processed appropriately according to the type of rubber products, etc. Specifically, ropes and cables containing glass fibers can be used to reinforce rubber products.
[0244] (Rope)
[0245] The rope (rubber reinforced rope) has the above-mentioned glass fibers (rubber reinforced fibers) gathered into a bundle of raw yarns. The number of glass fibers contained in the raw yarn is not particularly limited, for example, 100 to 2000, usually 200 to 600. The raw yarn can be formed by the following method: when the glass fiber is spun, a sizing agent commonly used in raw yarn formation, for example, an elastomer-based sizing agent, is used to gather a specified number of glass fibers that have been spun into a bundle. The formed raw yarn can be wound on a chuck or the like, and can also be subjected to a specified treatment such as drying.
[0246] The cable preferably has a plurality of strands gathered into a bundle to form a strand assembly. However, the strand forming the cable may also be one strand. Preferably, the strand or strand assembly contains 200 to 36,000 glass fibers, more preferably 200 to 7,800 glass fibers. In addition, the strand or strand assembly preferably has a diameter of 10 tex to 8,350 tex, more preferably 68 tex to 1,430 tex.
[0247] In the rope, the raw yarn can be coated with a first coating layer formed by a treatment liquid A, wherein the treatment liquid A contains at least one selected from resorcinol-formaldehyde condensate and a vulcanizing agent and an emulsion. By coating the raw yarn with the first coating layer, the adhesion between the rope and the base rubber embedded in the rope can be improved. The first coating layer can be coated with one raw yarn or a raw yarn aggregate formed by bundling two or more raw yarns.
[0248] The type of emulsion is not particularly limited, and for example, it may be at least one selected from vinylpyridine-styrene-butadiene polymer (VP) emulsion, chlorosulfonated polyethylene (CSM) emulsion, acrylonitrile-butadiene polymer (NBR) emulsion, and a highly saturated polymer emulsion containing a nitrile group. By using these materials, the heat resistance and water resistance of the reinforcing rope can be improved. In addition, as highly saturated polymers containing a nitrile group, copolymers containing acrylonitrile as a structural unit such as hydrogenated NBR (H-NBR) and hydrogenated terpolymers, or materials containing acrylonitrile and saturated hydrocarbons as structural units such as butadiene-ethylene-acrylonitrile terpolymers, etc. can be cited.
[0249] The resorcinol-formaldehyde condensate (RF) is not particularly limited, and Novolak type, Resol type, or a mixed type thereof can be used. The molar ratio of resorcinol (R) to formaldehyde (F) in RF is preferably R:F=1:1 to 3. RF is generally sold as a liquid containing a solid component, and a solid component content in the range of about 5% by weight to 10% by weight can be appropriately used.
[0250] The vulcanizing agent is not particularly limited, and for example, at least one selected from maleimide compounds and organic diisocyanate compounds can be cited. When the treatment liquid A contains a vulcanizing agent, the content of the vulcanizing agent in the treatment liquid A can be in the range of 5 to 100 parts by weight, preferably in the range of 20 to 75 parts by weight, relative to 100 parts by weight of the solid content of the emulsion. In this case, the balance between the bendability of the rope and the adhesion to the base rubber can be made better.
[0251] The organic diisocyanate compound is not particularly limited, and examples thereof include hexamethylene diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), toluene diisocyanate, xylene diisocyanate, naphthalene diisocyanate, and methylenebis(phenyl isocyanate).
[0252] The treatment liquid A may contain one or more of these organic diisocyanate compounds, and may be a mixture of isomers related to the substituents, such as toluene diisocyanate and methylene bis (phenyl isocyanate). In addition, the organic diisocyanate compound may be used in a state where its isocyanate group is protected by phenols or lactams.
[0253] The maleimide compound is not particularly limited, and for example, bismaleimide, phenylmaleimide, diphenylmethane-4,4′-bismaleimide, or the like may be used.
[0254] The solid content in the treatment liquid A is preferably in the range of 10 wt% to 40 wt%, more preferably in the range of 25 wt% to 35 wt%. If the content is too small, the first coating layer is insufficiently formed, and if it is too large, it is difficult to control the amount of treatment liquid A applied to the precursor, and the thickness of the first coating layer tends to become uneven.
[0255] The treatment liquid A may also contain alkalis such as ammonia for adjusting pH as required, and may also contain stabilizers, anti-aging agents, etc. The treatment liquid A may also contain fillers such as carbon black, in which case a rope with better adhesion to the matrix rubber can be made.
[0256] When forming the first coating on the raw yarn, the method commonly used in the production of ropes can be applied. For example, the raw yarn (including the aggregate) is continuously immersed in a coating bath containing the treatment liquid A, and after the raw yarn is pulled out of the coating bath, the excess treatment liquid is removed and dried as necessary. The raw yarn formed with the first coating can be used as a rope directly, or it can be subjected to various treatments such as twisting and forming a second coating layer as described later as needed.
[0257] The first covering layer may be formed in an amount corresponding to about 10% to 30% by weight based on the weight of the original yarn.
[0258] The cable may also have a structure in which two or more original filaments covered by the first coating layer are bundled into a bundle by applying a lower twist, and then a top twist is applied to the bundle. In this case, the strength is further improved, and a cable with better bending fatigue resistance can be made. The number of times of the lower twist can be about 0.5 to 4 times per 2.54 cm (1 inch) in the length direction, preferably about 1.2 to 3 times. After the wires formed by the lower twist are bundled into a bundle, 0.5 to 4 times, preferably 1 to 2.8 times, can be applied to the top twist every 2.54 cm in the length direction.
[0259] The rope may also be coated with a second coating layer containing rubber. In this case, the rope can be made with further improved adhesion to the base rubber.
[0260] The type of rubber is not particularly limited and can be appropriately selected according to the type of base rubber, etc. For example, when the base rubber is a highly saturated polymer containing a nitrile group, it is preferred that the second coating layer contains CSM as the rubber from the viewpoint of better adhesion. In addition, for example, when the base rubber is a mixed rubber in which zinc polymethacrylate (ZDMA) is dispersed in a highly saturated polymer containing a nitrile group, it is preferred that the second coating layer contains a highly saturated copolymer containing a nitrile group or a mixed rubber having the same composition as the base rubber as the rubber from the viewpoint of better adhesion.
[0261] The second coating layer can be formed by, for example, immersing the original yarn (including the aggregate), the original yarn (including the aggregate) coated with the first coating layer, or the yarn obtained by further twisting the original yarn in the treatment liquid B in which rubber or a rubber precursor is dissolved, and then drying. Since CSM and highly saturated polymers containing nitrile groups are soluble in aromatic hydrocarbons such as benzene, toluene, and xylene, halogenated hydrocarbons such as trichloroethylene, ketones such as methyl ethyl ketone, and esters such as ethyl acetate, the treatment liquid B may also contain these organic substances as solvents.
[0262] The treatment liquid B may contain a vulcanizing agent. For example, in addition to the above-mentioned maleimide compounds and organic diisocyanate compounds, sulfur, organic peroxides such as diisopropyl peroxide and 1,3-bis(tert-butylperoxy-m-isopropyl)benzene, aromatic nitroso compounds such as p-dinitronaphthalene and p-dinitrosobenzene, etc., may be used as the vulcanizing agent. The treatment liquid B may also contain an inorganic filler, an anti-aging agent, a vulcanizing aid, a plasticizer, etc., as required.
[0263] The content of substances other than the solvent (rubber, vulcanizing agent, etc.) in the treatment liquid B can be appropriately set according to the type of the substance. If it is in the range of about 3% by weight to 25% by weight, preferably in the range of about 5% by weight to 15% by weight, the second coating layer can be easily formed. The content of rubber or rubber precursor in the substances other than the solvent is preferably about 20% by weight to 60% by weight. When the treatment liquid B contains a vulcanizing agent, the content of the vulcanizing agent in the substances other than the solvent is preferably in the range of about 0.5% by weight to 30% by weight.
[0264] When forming the second coating layer, for example, about 1 wt % to 15 wt %, preferably about 2 wt % to 6 wt %, of the treatment liquid B is attached to the surface of the original yarn (including the aggregate) or the twisted yarn, calculated as the amount of substances other than the solvent, relative to the weight of the original yarn.
[0265] Examples of rubber products reinforced by the above-mentioned ropes include rubber belts, rubber tires, and rubber tubes. An example of a rubber belt is a transmission belt. Examples of transmission belts include meshing transmission belts and friction transmission belts. An example of a meshing transmission belt is a toothed belt represented by a timing belt for an automobile. Examples of friction transmission belts include flat belts, round belts, V-belts, and V-belt ribbed belts. The rubber tire is typically an automobile tire or a bicycle tire. Among the reinforcing ropes used for rubber products, glass fiber is particularly preferred because it has an excellent elastic modulus.
[0266] Figure 8 An example of the structure of a rubber belt including cords is shown in FIG. The rubber belt 91 has a so-called toothed belt shape, and includes a base rubber 93 and a plurality of cords 92 embedded in the base rubber 93. The cords 92 are arranged parallel to each other along the longitudinal direction of the rubber belt 91, in other words, in a direction perpendicular to the belt width direction across which the protrusions 94 constituting the "teeth" cross. A tooth cloth 95 is attached to the surface of the rubber belt 91 on which the protrusions 94 are formed for the purpose of suppressing wear and the like.
[0267] (other)
[0268] Glass fiber or glass filler can also be processed into other forms other than the above-mentioned ropes and used. As other forms, the above-mentioned forms about concrete products can be cited.
[0269] <Reinforcement of plastic products>
[0270] As mentioned above, glass fibers and glass fillers can be used to reinforce plastic products (resin products). From another aspect, the present invention provides a plastic product having at least one selected from the group consisting of glass fibers and glass fillers of the present embodiment. In a preferred embodiment, the plastic product has a resin composition (matrix resin), and glass fibers or glass fillers embedded in the resin composition. In another preferred embodiment, the plastic product has a main body, and a covering member covering the surface of the main body, and the covering member contains glass fibers or glass fillers. The covering member may also contain materials such as resin. Plastic products reinforced with glass fibers are called FRP (Fiber Reinforced Plastic).
[0271] The matrix resin may contain a thermosetting resin or a thermoplastic resin. The thermosetting resin is not particularly limited, and examples thereof include epoxy resins, modified epoxy resins such as vinyl ester resins, phenolic resins, unsaturated polyester resins, polyimide resins, bismaleimide resins, and the like. The thermoplastic resin is not particularly limited, and examples thereof include polyolefin resins, polyamide resins, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone resins, and the like. Resin products containing thermoplastic resins can be easily manufactured by injection molding, stamping molding, and the like.
[0272] Glass fillers (especially chopped strands) can also be used to reinforce plastic products. Glass fibers and glass fillers used to reinforce plastic products can be appropriately processed according to the type of plastic products. In detail, fiber sheets containing glass fibers and glass fillers can be used to reinforce plastic products. Glass fibers or glass fillers can also be processed into other forms other than chopped strands and fiber sheets. As other forms, the above-mentioned forms for concrete products can be cited.
[0273] The glass fiber or glass filler reinforced plastic product of this embodiment can be used for applications such as sporting goods, vehicles such as automobiles, ships, building materials, airplanes, septic tanks, bathtubs, blades for wind power generation, angle materials, poles, containers, pipes, sewer pipes (drain pipes), fuel tanks, and home appliances.
[0274] Examples of plastic products for sporting goods include fishing lines, fishing rods, golf club handles, skis, kayaks, tennis / badminton rackets and strings, etc. Examples of plastic products for vehicle use include vehicle bodies, lampshades, front panels, bumpers, seat shells, drive shafts, etc. Examples of plastic products for ship use include ship bodies, masts, decks, etc. Examples of plastic products for aircraft include primary structural materials, secondary structural materials, interior materials, seats, and accessory components, etc. Examples of plastic products for home appliances include substrates, panels, switch devices, insulators, and home appliance bodies, etc.
[0275] In plastic products used in natural environments, such as drainage pipes, glass fibers and glass fillers come into contact with acidic liquids such as acid rain. Therefore, in this application, glass fibers and glass fillers are particularly preferred because of their excellent acid resistance. Glass fibers and glass fillers also need to have sufficient elastic modulus for practical use.
[0276] Furthermore, the glass fiber and glass filler of this embodiment can also be used for mufflers and engine parts of vehicles, and high-temperature heat insulating materials used in blast furnaces, etc. The glass fiber and glass filler of this embodiment can also be used for separators used in batteries such as lead-acid batteries.
[0277] Example
[0278] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples.
[0279] [Examples 1 to 31 and Comparative Examples 1 to 11]
[0280] The raw materials of a common glass composition such as silicon dioxide were weighed and mixed to a homogeneous state so as to achieve the compositions shown in Tables 2 to 6 (the unit of the content of the components is mass %), and a raw material mixed batch was prepared. In particular, in Examples 1 to 31 and Comparative Examples 1 to 8, fly ash, silicon dioxide, aluminum oxide, boron trioxide, magnesium oxide, calcium carbonate, strontium carbonate, zinc oxide, lithium carbonate, sodium carbonate, potassium carbonate, titanium dioxide, zirconium oxide, and iron trioxide were used. The composition of the fly ash used is shown in Table 1.
[0281]
Table 1
[0282]
[0283] Next, the prepared raw material mixture batch was melted at 1500-1600°C using an electric furnace and maintained in a molten state for about 4 hours to make the composition uniform. Afterwards, a portion of the obtained molten glass composition (glass melt) was poured onto an iron plate and slowly cooled to room temperature in the electric furnace to obtain a block-shaped glass composition sample (plate-shaped) for evaluation.
[0284] The Young's modulus E, working temperature, mass loss rate ΔW1 in an acidic solution, and mass loss rate ΔW2 in an alkaline solution of the prepared glass composition sample (hereinafter referred to as sample) were measured. The measurement method is as follows.
[0285] <Measurement of Young's modulus>
[0286] The sample was cut, each surface was mirror-polished to prepare a plate-shaped sample of 25×25×5 mm, and the density ρ of the sample was measured by the Archimedean method. In addition, the Young's modulus was measured according to the ultrasonic pulse method of JIS R1602-1995. Specifically, the sound velocity of the ultrasonic pulse propagation was measured for the longitudinal wave and the transverse wave using the sample used in the aforementioned density measurement, and the Young's modulus was calculated by substituting the sound velocity of the ultrasonic pulse propagation into the following formula together with the aforementioned density. In addition, the propagation velocity was calculated by using an ultrasonic thickness gauge MODEL 25DL PLUS manufactured by Olympus Corporation, using the time it takes for an ultrasonic pulse with a frequency of 20 kHz to propagate and reflect in the direction of the sample thickness and divided by the propagation distance (twice the thickness of the sample).
[0287] E=3ρ·v t 2 ·(v l 2 -4 / 3·v t 2 ) / (v l 2 -v t 2 )
[0288] E: Young's modulus (GPa)
[0289] ρ: density (kg / m 3 )
[0290] v l : Longitudinal wave velocity (m / s)
[0291] v t : Shear wave velocity (m / s)
[0292] <Measurement of glass transition temperature>
[0293] The average linear expansion coefficient of the obtained glass composition was measured using a commercially available dilatometer [Temperature Mechanical Analyzer, TMA8510, manufactured by Rigaku Corporation], and the glass transition temperature was obtained based on the thermal expansion curve obtained by the TMA apparatus.
[0294] <Measurement of operating temperature>
[0295] The relationship between viscosity and temperature of the obtained glass composition was investigated by a conventional platinum ball pulling method, and the working temperature was obtained based on the result. Here, the so-called platinum ball pulling method is a method of measuring viscosity by applying the relationship between the load (resistance) when the platinum ball is pulled up by uniform motion and the gravity and buoyancy acting on the platinum ball to Stokes' law, which represents the relationship between viscosity and falling speed when tiny particles settle in a fluid.
[0296] <Measurement of mass loss rates ΔW1 and ΔW2>
[0297] The mass loss rates ΔW1 and ΔW2 were measured in accordance with the standard “Measurement method for chemical durability of optical glass (powder method)” (JOGIS 06) established by the Japan Optical Glass Industries Association.
[0298] (Measurement of mass loss rate ΔW1 in acidic solution)
[0299] The measurement was performed according to the following procedure.
[0300] 1. Grind a glass composition sample.
[0301] 2. The pulverized sample is passed through a 600 μm test sieve, and the powder sample whose size remains on a 425 μm test sieve is selected. The test sieve is specified in JIS Z8801.
[0302] 3. Weigh 5 g of the sorted powder sample.
[0303] 4. The weighed powder sample was immersed in 80 mL of a 21.2 mass % sulfuric acid aqueous solution at 99° C. for 1 hour.
[0304] 5. After immersion, remove the supernatant by tilting (decantation), dry the remaining sample, and measure its mass.
[0305] 6. The mass loss rate ΔW1 is calculated as the ratio of the difference between the mass of the sample and the mass of the remaining sample to the mass of the sample before immersion in the aqueous sulfuric acid solution.
[0306] As mentioned above, ΔW1 is an indicator of acid resistance.
[0307] (Measurement of mass loss rate ΔW2 in alkaline solution)
[0308] The measurement was performed according to the following procedure.
[0309] 1. Grind a glass composition sample.
[0310] 2. The pulverized sample is passed through a 600 μm test sieve, and the powder sample whose size remains on a 425 μm test sieve is selected. The test sieve is specified in JIS Z8801.
[0311] 3. Weigh 5 g of the sorted powder sample.
[0312] 4. The weighed powder sample was immersed in 80 mL of a 10 mass % sodium hydroxide aqueous solution at 99° C. for 1 hour.
[0313] 5. After immersion, remove the supernatant by tilting (decantation), dry the remaining sample, and measure its mass.
[0314] 6. The mass loss rate ΔW2 is calculated as the ratio of the difference between the mass of the sample and the mass of the remaining sample to the mass of the sample before immersion in the sodium hydroxide aqueous solution.
[0315] As mentioned above, ΔW2 is an indicator of alkali resistance.
[0316] Tables 2 to 6 show the Young's modulus, glass transition temperature, working temperature, mass loss rate ΔW1 in an acidic solution, and mass loss rate ΔW2 in an alkaline solution of the glass composition.
[0317]
Table 2
[0318]
[0319]
Table 3
[0320]
[0321]
Table 4
[0322]
[0323]
Table 5
[0324]
[0325]
Table 6
[0326]
[0327] As shown in Tables 2 to 4, the glass compositions of Examples 1 to 31 have Young's moduli in the range of 89 to 94 GPa, mass loss rates ΔW1 in acidic solutions in the range of 0.02 to 0.17 mass %, and mass loss rates ΔW2 in alkaline solutions in the range of 0.03 to 0.18 mass %. Thus, the glass compositions of the Examples have high elastic moduli and improved acid and alkali resistance.
[0328] In contrast, the glass composition of Comparative Example 1 has Al2O3 / (SiO2+Al2O3) of 0.17, which is higher than 0.15. The glass composition of Comparative Example 1 has a mass loss rate ΔW2 of 0.22% by mass in an alkaline solution, and is inferior in alkali resistance to the glass compositions of Examples 1 to 31.
[0329] The glass composition of Comparative Example 2 had Al2O3 / (SiO2+Al2O3) of 0.03, which was lower than 0.05. In Comparative Example 2, the glass composition was phase-separated, and a homogeneous glass material was not obtained.
[0330] The glass composition of Comparative Example 3 has a T-Fe2O3 content of 25.8% by mass, which is higher than 25% by mass. The glass composition of Comparative Example 3 has a mass loss rate ΔW1 of 0.38% by mass in an acidic solution, which is inferior to the glass compositions of Examples 1 to 22 in acid resistance. In addition, the glass composition of Comparative Example 3 has a mass loss rate ΔW2 of 0.21% by mass in an alkaline solution, which is inferior to the glass compositions of Examples 1 to 31 in alkali resistance.
[0331] The glass composition of Comparative Example 4 had a T-Fe2O3 content of 9.9% by mass, which was less than 10% by mass. In Comparative Example 4, the glass composition was phase-separated, and a homogeneous glass material was not obtained.
[0332] The glass composition of Comparative Example 5 has a T-Fe2O3 content of 9.6% by mass, which is less than 10% by mass. In Comparative Example 5, the glass composition has a Young's modulus of 87 GPa, which is lower in elasticity than the glass compositions of Examples 1 to 31.
[0333] The glass composition of Comparative Example 6 had Al2O3 / (SiO2+Al2O3) of 0.03, which was lower than 0.05. In Comparative Example 6, the glass composition was phase-separated, and a homogeneous glass material was not obtained.
[0334] The glass composition of Comparative Example 7 had a B2O3 content of 11.9% by mass, which was higher than 10% by mass. In Comparative Example 7, a crystal phase was precipitated in the glass composition, and a homogeneous glass material was not obtained.
[0335] The glass composition of Comparative Example 8 has SiO2+Al2O3 of 66.3% by mass, which is higher than 66% by mass. In addition, the glass composition of Comparative Example 8 does not contain MgO, and MgO / (MgO+CaO) is 0. In Comparative Example 8, the Young's modulus of the glass composition is 88 GPa, which is lower in elasticity than the glass compositions of Examples 1 to 31. In Comparative Example 8, the working temperature of the glass composition is 1203°C, which is higher than the glass compositions of Examples 1 to 31.
[0336] The glass composition of Comparative Example 9 having a composition equivalent to conventional C glass had a mass loss rate ΔW1 of 0.10 mass % in an acidic solution and a Young's modulus of 78 GPa, which was lower in elasticity than the glass compositions of Examples 1 to 31.
[0337] The glass composition of Comparative Example 10 having a composition equivalent to that of conventional E glass has a Young's modulus of 83 GPa, which is lower in elasticity than the glass compositions of Examples 1 to 31. In addition, the glass composition of Comparative Example 10 has a mass loss rate ΔW2 of 0.27% by mass in an alkaline solution, and is inferior in alkali resistance to the glass compositions of Examples 1 to 31.
[0338] The glass composition of Comparative Example 11 having a composition equivalent to conventional alkali-resistant glass (AR glass) has a Young's modulus of 84 GPa, which is lower in elasticity than the glass compositions of Examples 1 to 31.
[0339] Industrial Applicability
[0340] The glass composition of the present invention has a high elastic modulus and improved acid and alkali resistance, so it is useful as a filler for glass flakes, chopped strands, milled fibers, glass powder, glass beads, etc. in addition to structural members. It is also particularly useful as a filler for cement because of its alkali resistance and high elasticity.
Claims
1. A glass composition, wherein: The contents of SiO2, Al2O3, B2O3, CaO and T-Fe2O3 are 50 mass%≤SiO2+Al2O3≤66 mass%, 0 mass%≤B2O3≤10 mass%, 5 mass%≤CaO≤30 mass%, 10 mass%<T-Fe2O3≤25 mass%, The mass ratio calculated from Al2O3 / (SiO2+Al2O3) is 0.05 or more and less than 0.15, The mass ratio calculated from MgO / (MgO+CaO) is 0.001 or more and 0.20 or less.
2. The glass composition according to claim 1, wherein The content of SiO2 is 45 mass %≤SiO2≤62 mass %.
3. The glass composition according to claim 1, wherein The content of B2O3 is 0.1 mass %≤B2O3≤10 mass %.
4. The glass composition according to claim 1, wherein The content of MgO is 0.1 mass % ≤ MgO ≤ 10 mass %.
5. The glass composition according to claim 1, wherein The content of SrO is 0.1 mass % ≤ SrO ≤ 15 mass %.
6. The glass composition according to claim 1, wherein: The content of TiO2 is 0.1 mass %≤TiO2≤10 mass %.
7. The glass composition according to claim 1, wherein: The content of ZrO2 is 0.1 mass % ≤ ZrO2 ≤ 10 mass %.
8. The glass composition according to claim 1, wherein: The content of Li2O, Na2O and K2O is 0.1 mass %≤Li2O+Na2O+K2O≤5 mass %.
9. The glass composition according to claim 1, wherein: The content of SiO2 and B2O3 is 50 mass%≤SiO2+B2O3≤66 mass%.
10. The glass composition according to claim 1, wherein The content of T-Fe2O3 is 11 mass %≤T-Fe2O3≤25 mass %.
11. The glass composition according to claim 1, wherein: Contains fly ash as raw material. 12 . A glass fiber comprising the glass composition according to claim 1 .
13. The glass fiber according to claim 12, wherein Used for reinforcement of concrete products, rubber products or plastic products. 14 . A glass filler comprising the glass composition according to claim 1 .
15. The glass filler according to claim 14, wherein Used for reinforcement of concrete products, rubber products or plastic products.
16. The glass filler according to claim 14, wherein The glass material is at least one selected from the group consisting of flake glass, chopped strands, milled fibers, glass powder and glass beads.
17. The glass filler according to claim 16, wherein It is flaky glass.
18. The glass filler according to claim 16, wherein It is chopped strands.
19. The glass filler according to claim 16, wherein It is ground fiber.
20. A method for producing glass fiber, wherein: Including the following processes: A step of melting the glass composition according to any one of claims 1 to 11; The molten glass composition is spun to form glass fibers.
21. A method for producing a glass filler, wherein: Including the following processes: A step of melting the glass composition according to any one of claims 1 to 11; A step of forming the molten glass composition into a glass filler.
Citation Information
Patent Citations
Reinforcement method for concrete utility pole and concrete utility pole
JP2006002543A
High modulus glass fiber composition made from basalt
JP2020529378A
Cited By
Low-erosion glass fiber and preparation method thereof
CN120664775A
A low-erosion glass fiber and a method for making the same
CN120664775B